Efeito do treinamento aeróbico com baixa carga e restrição de fluxo sanguíneo durante o exercício e precondicionante em diferentes ergômetros na potência aeróbia e anaeróbia - Lucena, Pedro Henrique Marques de (2019)
Aerobic Training (TA) is an effective way to improve the aerobic (PtA) and anaerobic power (PtAn) performance. In regard to the improvement of the aerobic and anaerobic characteristics induced by (TA), an intensity of 60% to 85% of the maximum oxygen volume (VO2max) is recommended. However, the technique of Blood Flow Restriction (RFS) during exercise is an alternative to induce changes in performance even when associated with low load training. Although the RFS technique is mostly associated with use in conjunction with physical exercise, some researchers have applied the technique without movement, which is called Preconditioning Ischemia (IPC). The aim of this study was to analyze the acute and chronic effect of low load aerobic training and blood flow restriction during exercise and preconditioning in different ergometers on PtA and PtAn. This is a quasi-experimental, longitudinal, randomized clinical trial, in which n = 23 sedentary subjects (30.0 ± 5.57 years) were divided into three groups: TABI + RFS – TA at 50% of VO2max with 50% RFS; IPC + TABI – TA at 50% of VO2max with 220mmHg of RFS; TABI – TA without RFS. The intervention lasted 4 weeks, 3 sessions / week, duration per session: 70 minutes, in which the groups performed low intensity aerobic exercises on three different ergometers, 6 minutes with 45 seconds interval between them and with order randomly pre- determined (vertical cycle ergometer, step and treadmill). For statistical analysis, the Shapiro-Wilk test was used to verify the normality of the data and one-way ANOVA and two-way ANOVA with Tukey or Kruskal-Wallis post-hoc for the analysis of possible differences in the variables of interest. The analysis was performed in R version 3.6.0 with significance value p≤0.05. No significant differences in PtA were observed at pre-post moments, nor between ergometers. Regarding PtAn, there was no increase in power peak or fatigue index. There was a significant difference in blood lactate increase only in the IPC + TABI group (p≤0.002). It was concluded that IPC + TABI is effective for improving physical performance of sedentary apparently healthy young men and it is superior than RFS + TABI and TABI on the variable: blood lactate.